Epidemiology and pathophysiology of venous thromboembolism: similarities with atherothrombosis and the role of inflammation - Riva, Nicoletta; Donadini, Marco P.; Ageno, Walter (Thrombosis and Haemostasis, 2015)
Venous thromboembolism (VTE) is a multifactorial disease. Major provoking factors (e. g. surgery, cancer, major trauma, and immobilisation) are identified in 50–60 % of patients, while the remaining cases are classified as unprovoked. However, minor predisposing conditions may be detectable in these patients, possibly concurring to the pathophysiology of the disease, especially when co-existing. In recent years, the role of chronic inflammatory disorders, infectious diseases and traditional cardiovascular risk factors has been extensively investigated. Inflammation, with its underlying prothrombotic state, could be the potential link between these risk factors, as well as the explanation for the reported association between arterial and venous thromboembolic events.
Keywords: Venous thromboembolism; etiopathogenesis; inflammation; atherothrombosis